ChemInform Abstract: Synthesis of 2‐(2‐Fluorophenyl)‐2‐methylamino‐cyclohexanone as a New Ketamine Derivative. Issue 48 (2nd December 2014) - Moghimi, Abolghasem; Rahmani, Siyavash; Zare, Reza; Sadeghzadeh, Morteza
Abstract A four‐step synthetic method for the synthesis of the title compound (VII) involving a Pd‐catalyzed rearrangement as the key step is presented.